Genetic Control of Root System Development in Maize. (January 2018) - Hochholdinger, Frank; Yu, Peng; Marcon, Caroline
Abstract : The maize root system comprises structurally and functionally different root types. Mutant analyses have revealed that root-type-specific genetic regulators intrinsically determine the maize root system architecture. Molecular cloning of these genes has demonstrated that key elements of auxin signal transduction, such as LOB domain (LBD) and Aux/IAA proteins, are instrumental for seminal, shoot-borne, and lateral root initiation. Moreover, genetic analyses have demonstrated that genes related to exocytotic vesicle docking, cell wall loosening, and cellulose synthesis and organization control root hair elongation. The identification of upstream regulators, protein interaction partners, and downstream targets of these genes together with cell-type-specific transcriptome analyses have provided novel insights into the regulatory networks controlling root development and architecture in maize. Trends: The maize root system comprises different root types formed at different stages of development with distinct anatomic and functional properties. Genetic analyses have demonstrated that genes involved in auxin signal transduction are key elements for the initiation of the seminal, lateral, and shoot-borne roots of maize. High-resolution tissue- and cell-type-specific transcriptome studies have identified genes and molecular pathways associated with the initiation of seminal, lateral, and shoot-borne roots. Genetic analyses have demonstrated that genes involved in exocytotic vesicle fusion and cellulose synthesis are instrumental for root hair elongation.